Ability to Use Information and Communication Technology Akidah Akhlak Teachers in Increasing Student Learning Outcomes in Madrasah Aliyah Negeri 2 City of Jambi - Rahmiyati Rahmiyati; Musa Musa; Darma Putra (Dinasti Publisher, 2022)
This research was conducted at MAN 2 Jambi City. This study focuses on the ability to use ICT for Akhlaq teachers in improving student learning outcomes, teachers' obstacles in using ICT and teachers' efforts in overcoming these obstacles. This research was conducted on Akhlaq teachers and students of class x Man 2 Jambi City Academic year 2021/2022 . This study uses a qualitative approach. The process of data collection is done through observation, interviews, and documentation. The results of the study on the ability to use ICT for Akhlak Teachers in MAN 2 Jambi City that there are two indicators about the ability to use ICT teachers, namely the ability to use hardware and software ICT media, the ability to use ICT for Akidah Akhlak teachers in MAN 2 class x that the Akidah Akhlak teachers have able to use hardware and software ICT media but the implementation is still not optimal due to several obstacles. In improving student learning outcomes for the tenth grade Akidah Akhlak subject at MAN 2 Jambi City, ICT media are used in the form of: Lapto, infokus, speakers, powerpoit alikasi, google and youtube as a support in the learning process. The obstacles faced by teachers in the use of ICT to improve student learning outcomes at MAN 2 Jambi City are: first, the information technology and communication skills of teachers' morals and beliefs that must be improved, secondly, the facilities are still insufficient. Efforts to overcome the obstacles faced in the use of information and communication technology to improve student learning outcomes at Madrasah Aliyah Negeri 2 Jambi City are increasing cooperation by increasing discussions, attending training on ICT and motivation to increase the desire to improve abilities.